Diagnosis of diseases of the facial area of the CT scan examination method (The Peerian Journal, 2025)
Computed tomography examination method is one of the modern diagnostic methods in medicine, which allows to show the internal structure of the human body clearly and in detail. The CT method is especially important in detecting diseases of the face. Diseases of the face can occur for various reasons, including injuries, tumors, inflammatory processes, infections and other pathological conditions. This article provides information about the role and importance of computer tomography in the diagnosis of facial diseases